Eco-friendly production of thermostable, halotolerant and pH wide range biosurfactant by Issatchenkia orientalis UCP 1603 (Research, Society and Development, 2022)
Microbial surfactants are amphiphilic molecules with attractive industrial prospects due to their advantages over commonly commercialized chemical surfactants, such as low toxicity, high biocompatibility and biodegradability, and efficiency at extreme conditions. However, the large-scale production of biosurfactants still becomes uncompetitive due to the low yields and onerous costs, being considered the use of renewable substrates as a viable strategy. In this sense, the present study aimed to investigate the sustainable production of biosurfactant by the yeast Issatchenkia orientalis UCP 1603 in 2 L of salt-based medium supplemented with 7.5% cassava wastewater, 5% corn steep liquor and 1% post-frying soybean oil. Fermentation was carried out in 2.8 L-Fernbach flasks for 72 h, at 28°C and 150 rpm, and reduction in surface tension to 30.1 mN/m was verified. The highest yield of the biosurfactant produced (4.02 g/L) was observed after extraction with 70% ethanol (2:1, v/v) and the isolated biosurfactant reduced the surface tension of the medium to 28.7 mN/m, the interfacial tension against n-hexadecane to 16.6 mN/m and has a CMC of 800 mg/L. The biocompound showed anionic and polymeric nature and did not present toxicity against cabbage (Brassica oleracea var. capitata) seeds. The stability in the range of pH 4-10, salinity 5-25% and temperature 5-100°C, evidenced a highly stable biosurfactant, with promising potential of application in several industrial activities or environmental processes in adverse conditions.